The Legislature and Political Development: A Comparison between Korea and Mongolia - Ж.ТӨРТОГТОХ (Politology, 2023)
In a democratic system, parliament is, on one hand, a representative institution of the people and, on the other hand, exists with a status of a political institution as a policy-making and law-making body. It is guaranteed by the Constitution. In addition legislature serves for political systems actively and becomes its dynamic expression. Parliamentary institution plays a tremendous role in and influences heavily on the political development. In this work, first, the author will consider general overview of constitutional systems of two countries. Then the author will discuss about the role and the status of parliament in the political system from their historical and functional sides, providing it with some patterns of the legislative institution. Moreover, electoral system and last election results, political parties’ seat ratio in parliament and the level of the voter turnout or citizen participation in the elections will be introduced here as well. Finally, it will cover the issues of the legislature’s effects in the political development and the process of strengthening of democracy and, furthermore, what potentials it will contain in further democratic process.